The Role of Futuristic Pedagogy in Building Character among Elementary School Students - Mulyati, Sri Entang; Herlambang, Yusuf Tri (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
The moral crisis affecting students in the digital era requires innovation in character education strategies. This study focuses on futuristic pedagogy as an approach capable of addressing these challenges, particularly in elementary schools. The research employs a descriptive qualitative method by combining a systematic literature review with semi-structured interviews with teachers. The findings reveal that futuristic pedagogy is not solely oriented toward the use of technology but also emphasizes the integration of ethical, spiritual, and humanistic values in the learning process. Four key findings emerge: the need for value-based curriculum reformulation, the repositioning of teachers as facilitators and agents of change, the reinforcement of moral values within the digital context, and the synergistic involvement of families and communities in the educational ecosystem. From this synthesis, an integrative model of futuristic pedagogy is developed, combining noble values, technology, and local wisdom to cultivate students who are virtuous, adaptive, and competitive in the era of Society 5.0. This research contributes both theoretically and practically to strengthening sustainable character education in elementary schools.